Book Reviews (The Muslim world, 1995)
Book Reviewed in This Article: Modern Arabic Poetry In English Translation Infibulation: Female Mutilation in Islamic Northeastern Africa. Women In the Quran Traditions, and Interpretation. The Eloquence of Silence: Algerian Women in Question. Fundamentalism and Gender. The Challenge of Modernity: The Quest For Authenticity In the Arab World.